Phytochemical Evaluation And In Vitro Myometrial Inhibition Of The Methanol Extract And Partitioned Choroform Fraction Of Scoparia Dulcis Ijnn (Scrophulariacea) On The Non-Pregnant Rat Uterus - Okunrobo, Lucky O.; Owolabi, Omonfhelin J.; Ederhion, Vivien O. (The Nigerian Journal of Pharmacy, 2011)
Click the download to preview.